An in vitro model for Pelger-Huët anomaly: stable knockdown of Lamin B receptor in HL-60 cells - Olins, Ada L.; Ernst, Aurélie; Zwerger, Monika; Herrmann, Harald; Olins, Donald E. (Nucleus, 2010)
The principal human blood granulocyte (neutrophil) possesses a lobulated and deformable nucleus, important to facilitate rapid egress from blood vessels as these cells migrate to sites of bacterial or fungal infection. This unusual nuclear shape is a product of elevated levels of an integral membrane protein of the nuclear envelope lamin B receptor (LBR) and of decreased amounts of lamin A/C. In humans, a genetic deficiency of LBR produces Pelger-Huët anomaly, resulting in blood neutrophils that exhibit hypolobulated nuclei with redistributed heterochromatin. Structural changes in nuclear architecture occur during granulopoiesis within bone marrow. The exact mechanisms of this nuclear shape change and of heterochromatin redistribution remain largely unknown. As a tool to facilitate analysis of these mechanisms, a stable LBR knockdown subline of HL-60 cells was established. During in vitro granulopoiesis induced with retinoic acid, the LBR knockdown cells retain an ovoid shaped nucleus with reduced levels of lamin A/C; whereas, the parent cells develop lobulated nuclei. Macrophage forms induced in LBR knockdown cells by in vitro treatment with phorbol ester were indistinguishable from the parent cells, comparing both nuclear shape and attached cell morphology. The capability of differentiation of LBR knockdown HL-60 cells should facilitate a detailed analysis of the molecular relationship between LBR levels, granulocyte nuclear shape and heterochromatin distribution.
Gesehen am 12.10.2022